Chronotype and Chrononutrition Profiles in Adolescents Obesity - Danindra Andri Hidayat; Mifta Khudin; Titis Prawitasari (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2026)
Background: Adolescent obesity remains a major global public health challenge. Modern lifestyle factors that disrupt circadian rhythms may exacerbate metabolic dysregulation in adolescents. Chronotype, reflecting innate circadian preferences for sleep-wake and activity timing, and chrononutrition, which emphasizes the alignment of meal timing with circadian rhythms, have gained attention as potential determinants of obesity. However, evidence integrating chronotype and chrononutrition profiles with adolescent obesity remains limited. Therefore, this review aims to synthesize the current evidence on the roles of chronotype and chrononutrition in adolescents obesity. Discussion: Circadian rhythm regulates metabolic, hormonal, and behavioral processes through coordinated central and peripheral clocks. Variations in chronotype and disruptions in circadian alignment influence sleep patterns, meal timing, and metabolic regulation in adolescents. Evidence indicates that chronotype alone does not directly determine obesity risk; rather, its interaction with eating timing, sleep quality, and lifestyle behaviors plays a crucial role. Chrononutrition emphasizes aligning food intake with the biologically active phase, which is associated with improved insulin sensitivity, glycemic control, lipid metabolism, and blood pressure regulation. Determining chronotype and chrononutrition profiles remains challenging. The assessment is predominantly performed using standardized and validated questionnaires. Conclusion: Chronotype and chrononutrition profiles may contribute to the risk of obesity in adolescents. They might be a potential strategy for obesity prevention and management. Nevertheless, current evidence remains limited, and further longitudinal and interventional studies are required to confirm these findings and inform future recommendations.